An Analysis Classroom Interaction: A Case Study of International Class of Physic Department at Universitas Negeri Padang - Nabila, Shaza Inash; Ratmanida, Ratmanida (Universitas Negeri Padang, 2024)
This study examined classroom interactions within the International Class of the Physics Department at Universitas Negeri Padang, emphasizing both student attitudes and the characteristics of these interactions. A descriptive quantitative analysis was utilized, with data collected through observations, questionnaires, and interviews. The Flanders Interaction Analysis Categories System (FIACS) was employed to categorize the interactions between teachers and students. The sample comprised 15 students and one lecturer.The study emphasized fostering a positive and interactive classroom environment, revealing distinct interaction patterns: lecturers primarily engaged in explaining (44%) and questioning (28%), while students exhibited minimal instances of accepting feelings (11%) or giving directions (12%). Student interactions with lecturers involved more accepting feelings (33%) and responding (28%), along with questioning (16%) and initiation (23%). The study concludes that interactive teaching practices enhance the educational experience and suggests that encouraging critical engagement and improving teacher facilitation can further enrich classroom interactions and learning outcomes.